THE DISCOURCE OF LEARNING/TEACHING GOAL AND OBJECTIVES AS A TOPICAL DIDACTIC PROBLEM - Stonkuvienė, Irena; Nauckūnaitė, Zita (Acta Paedagogica Vilnensia, 2010)
The article discusses didactic problems of 12–14 year old learners’ learning/teaching that are related to establishment of goals and objectives of learning/teaching. The survey of 395 teachers of various subjects and 399 school learners from 6th–8th forms was carried out.The research reveals that the role of a learner as the main participant of the learning/teaching process is relatively declarative. Though four fifths of the school learners in the survey express willingness to be active participants in the process of learning, they do not have possibilities of active involvement in construction of their own knowledge; in the learning/teaching process school learners adjust to teachers’ requirements in a conformist way, whereas the latter do too little to change such a situation because declaring paradigms of learning and interaction in a more theoretical way, in many cases they act within the impact paradigm disregarding the spheres of didactic process that are topical to a learner. Only one fourth of teachers provide learners with a possibility to set up lesson goals and only one fourth of school learners have participated in making decisions regarding the content of learning. School learners, who lack opportunities for establishing lesson goals and planning their own activity, fail to acquire skills needed for this activity and, therefore, school learners expect and look forward to exact instructions from their teachers most frequently.Teachers still perceive establishment of goals as a preparatory stage of learning/teaching rather than a particularly important part of the learning/teaching process which develops school learners’ thinking, stimulating motivation which enables them to perceive and define their own needs and possibilities. There is a well-marked tendency to derive learning/teaching goals and objectives from learning/teaching content (almost all the teachers in the survey) or to take them from education documents (three thirds of teachers in the survey), which most frequently reveals a directive and formalised nature of learning/teaching goals.The answers to the question about obstacles to implement goals and objectives of learning/teaching show that the problems indicated by teachers do not coincide with the problems pointed out by school learners. More than three fourths of teachers see weak motivation of learners as the most frequent impediment to realisation of learning/teaching goals and objectives, more than a half of the teachers point out that an extremely broad content of learning/teaching and lack of teaching aids hinder this process. However, three fifths of school learners point out that the lack of discipline in the classroom is the biggest obstacle to achieve of goals set by a teacher or/and by a learner. More than half of the school learners state that their learning is mainly hindered by the fear to get a low mark, lack of concreteness of learning/teaching goals and too broad learning/teaching content.
Keywords: goals and objectives of learning/teaching; learning/teaching process; didactic problem